Astrobiologia: compreendendo a vida em seu contexto cósmico - Amaral, Cesar Rogério Leal do; Donato, Anna Luiza dos Santos; Goldenberg-Barbosa, Rodrigo; Anjos, Dafne Adriana Abreu dos (Revista Sustinere, 2023)
⠀⠀⠀⠀⠀⠀⠀⠀⠀